Alteration due to Prolonged Food Deprivation in Protein Content of Muscles and Brain of Clarias batrachus - Prasad, Nayan K. (Nepal Journal of Science and Technology, 2016)
The present paper deals with the impact of starvation on fish which has a great ability to adapt in the prolonged starvation condition. In the present investigation, the impact of starvation on protein contents of muscle and brain tissues has been observed in both the sexes of Clarias batrachus. The level of protein content was relatively higher in females than in males. The brain showed higher value of protein in normal condition (138mg/g in male and 153mg/g in female) in comparison to the muscles (132 mg/g in male and 140mg/g in female). During prolonged food deprivation, the gradual decrease in protein level has been noticed in all types of tissues which can be related to blocking of RNA synthesis, enhanced gluconeogenesis and increased rate of transamination and deamination. The maximum depletion has been observed in muscles (48% in male and 46% in female) and the least depletion in the brain (3% in male and 6% in female) after 40 days of starvation. Nepal Journal of Science and Technology Vol. 16, No.1 (2015) pp. 95-98